The institutional approach to the development of education in the social and investment model of Russia's economic growth - Krupnov, Yuriy A.; Yankovskaya, Veronika V.; Semenova, Elena I.; Semenov, Aleksandr V. (Frontiers in Education, 2023)
To develop an institutional approach to the development of education in the social and investment model of economic growth in developing countries by the example of Russia. The hypothetical and deductive principles and regression analysis are used in this research. The research results show that the social and investment model of economic growth is being implemented in the countries of the CIS and in Russia, and – as of now – the development of education slows down economic growth, instead of acceleration. To solve this problem, we offer an institutional approach to the development of education in the social and investment model of Russia's economic growth. The new approach allows for a flexible selection of measures of management depending on the needs of education’s development: development of only current, only future, or all workforce. The developed approach is based on the institution of the legal framework's adaptability to digital business models. Since workforce and skills play a key supporting role in digital business, the development of the institution of legal framework’s adaptability to digital business models will stimulate the development of higher education and will ensure Russia’s transition to the social and investment model of economic growth. For the practical application of the new approach, we develop an optimization model of institutional management in the interests of the development of education and transition to the social and investment model of economic growth in Russia.